Biological Rationale and Clinical Evidence of Carbon Ion Radiation Therapy for Adenoid Cystic Carcinoma: A Narrative Review - Loap, Pierre; Vischioni, Barbara; Bonora, Maria; Ingargiola, Rossana; Ronchi, Sara; Vitolo, Viviana; Barcellini, Amelia; Goanta, Lucia; De Marzi, Ludovic; Dendale, Remi; Pacelli, Roberto; Locati, Laura; et al. (Frontiers in Oncology, 2021)
Adenoid cystic carcinoma (ACC) is a rare, basaloid, epithelial tumor, arising mostly from salivary glands. Radiation therapy can be employed as a single modality for unresectable tumors, in an adjuvant setting after uncomplete resection, in case of high-risk pathological features, or for recurrent tumors. Due to ACC intrinsic radioresistance, high linear energy transfer (LET) radiotherapy techniques have been evaluated for ACC irradiation: while fast neutron therapy has now been abandoned due to toxicity concerns, charged particle beams such as protons and carbon ions are at present the beams used for hadron therapy. Carbon ion radiation therapy (CIRT) is currently increasingly used for ACC irradiation. The aim of this review is to describe the immunological, molecular and clinicopathological bases that support ACC treatment with CIRT, as well as to expose the current clinical evidence that reveal the advantages of using CIRT for treating ACC.